PERSEPSI MAHASISWA AKUNTANSI TERHADAP KEINGINAN UNTUK MELAKUKAN WHISTLEBLOWING (Studi Empiris Pada Mahasiswa Akuntansi Fakultas Ekonomi Dan Bisnis Di Universitas Islam Malang Dan Universitas Negeri Malang ) - Asril Ainun; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine student perceptions of the desire to do whistleblowing. Conducted at the Malang Islamic University and the Malang State University, this study used the Google Form application to distribute questionnaires to collect the required data and information. The independent variables used in this study are Attitudes to Behavior, Subjective Norms, Perceptions of Behavioral Control, Seriousness Levels of Fraud and the Dependent variable, namely Desire. In collecting data, the researcher used purposive sampling technique by determining several criteria by the researcher. Questionnaires were distributed and filled out by accounting students who had taken business ethics courses. The number of questionnaires distributed was 222 and collected as many as 180 respondents who were willing to fill out. The results of this study indicate that Attitude Towards Behavior, Perception of Behavioral Control and Seriousness of Fraud have a significant effect on the desire to do whistleblowing, while Subjective Norms do not significantly affect the desire to do whistleblowing.Keywords: Perception, Attitude to Behavior, Subjective Norm, Perception of Behavioral Control, Level of Seriousness of Cheating, Desire, Whistleblowing.